The escalation of the Second Karabakh War from the three levels of analysis perspective - Akhundzada, Nuray (ADA University, 2021)
Recently, the Nagorno Karabakh conflict underwent a complete transformation as a new full scale war broke out. Given its very nature of being a frozen conflict in the Post- Soviet space, escalation of the hostilities were not expected. Previous literature explains the factors that have led to the conflict’s being stacked in the negotiation process and failing to achieve a solution, and all of them disregarded the possibility of the future one. In this regard this paper aims at explaining how the second war came into existence by identifying the war triggering factors and how they were shifted just before the war. In doing so, the paper focuses on not a single cause as the previous literature did, but explores several factors existing at various levels to showcase the multifacetedness of the phenomenon. These factors are grouped into the individual, state and international levels. The study utilizes qualitative content analysis of the speeches of the presidents and heads of governments complemented with expert interviews. At an individual level, the research finds no change in the policy of the decision maker in Armenian side, excluding the alteration in his rhetoric and actions, but Azerbaijani side changed its approach to the conflict. At the international level, geopolitical shifts are mainly observed in Russian and Turkish sides. On a domestic level, Armenian side has gone through democratization while maintaining the previous perspective for the conflict. The role of the international system level factors have been more detrimental for the start of the war.
Keywords: Public and International Affairs; Nagorno Karabakh Conflict; Frozen Conflict; Caucasus, South--Ethnic relations.; Nagorno-Karabakh (Azerbaijan)--History.; Azerbaijan--Relations--Armenia (Republic)